Impact of Real Manipulation and Tax Compliance on Strategy Model: A Simulative Prediction of The Future Certainty - Muljanto Siladjaja (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
High awareness of obedience and compliance is a fundamental requirement in monitoring going concerned, reflecting a critical role of meaningful accounting information. This research tested earnings quality to measure belief and faith in achieving a sustainable business as optimism and confidence in the better one. The collecting data concerned the listed manufacturing company during 2010-2021, where purposive sampling and moderated regression with dummy variables were to capture the strategy topologies. The causal research observed amounted to 214 companies, illustrating that the number of valid observations has been 1.278 samples. The finding depicts the mapping of the investor reaction to quality accounting information related to this rational decision model in predicting the high future certainty as a positive signal. Bayes Teorema and Decision Tree Model are used to distinguish the prospective company as a highly guaranteed information; the social responsibility of the regulator is to minimize the distortion by implementing the going-private procedure for the low-prospected one; pragmatically, one platform of financial reporting service is to deduct a minimum chance for opportunity accruals. As a new insight into the literature in accounting, this simplex-linear programming has been modified into an innovative portfolio as an artificial intelligence model to maximize each utility.